If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 5) = 4 Reorder the terms: 2(5 + 3x) = 4 (5 * 2 + 3x * 2) = 4 (10 + 6x) = 4 Solving 10 + 6x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 6x = 4 + -10 Combine like terms: 10 + -10 = 0 0 + 6x = 4 + -10 6x = 4 + -10 Combine like terms: 4 + -10 = -6 6x = -6 Divide each side by '6'. x = -1 Simplifying x = -1
| 1/3m^2=-1/6m+1/2 | | 14+8x=6x-20+2x | | 4(x+3)=400 | | x-3/7=5/7 | | 3/2m=1/2 | | 0.09-15=5 | | 2.7y=y+1+1 | | 5x^2+5x-18=0 | | R-15=6 | | -6y=8-9+6y | | 2x+5y=-16 | | -2/5+x=2/5 | | 2.7y=1+1 | | 5s-1=6s | | x/3-1=5 | | z/3+7=9,5 | | -3y+2=8 | | 5/6a=5/8 | | -33-2=7-7x | | 7x+9-10x=-18 | | 3+2x=75 | | 2x+1y=1.70 | | 1/x+2/x+1 | | 3x-6=-9+25 | | 4r+9+r=-17-8r | | 5x=-10y+30 | | 7-4d=3d-9d+25 | | 0.333(b-9)=b+9 | | 3/4x=9 | | 7=34 | | -1/4x=7 | | 9(c+2)-11=5(2c+3)-2 |